Mentoring, educational services, and incentives to learn: What do we know about them? - Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2010)
This paper reviews recent studies on the effectiveness of services and incentives offered to disadvantaged youth. We focus our analysis on three types of interventions: mentoring, educational services, and financial rewards. The objective of this article is threefold. First, we explain alternative theoretical points of view in favor (or against - when applicable) each of these interventions. Then, we discuss how recent empirical work has affected that view, and we summarize the latest findings. We conclude with a discussion on what questions remain to be examined. Our hope is that this article will serve as a resource for those seeking to understand what educational interventions work and for whom, and to use as a starting point to illuminate the debate on where to go next.
Keywords: C93; I21; I22; I28; J24; 330; cognitive and non-cognitive skills; intrinsic and extrinsic motivation; at-risk youth; resilience; deviancy training; deterrence; primary- and high-school; post-secondary education; remedial programs; incentives on inputs and outputs